Analysis of migration in the largest cities of the Czech Republic - Sasek, Miloslav (Analiza migracji w największych miastach Republiki Czeskiej, 2011)
This text is focused on migration in the biggest cities in the Czech Republic. Suburbanization process was apparent in the second part of the 1990s primarily in the surrounding areas of Prague, Brno and Plzeň. The suburbanization did not as much accelerate in structurally affected areas – for example in the area of Moravian-Silesian city of Ostrava. During 1992-2003 (monitored period) Prague showed a negative migration balance (which continued until 2001). In Brno, which is minor in terms of population, the decrease of the inhabitants on account of relocation was noted in 1996 and in Plzeň even earlier in 1994. In both cities the negative migration balance continued until the end of the analyzed period, i.e. to the end of 2003 (in a matter of fact it was until 2004 in Plzeň and 2006 in Brno).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 180, s. 169-177
Keywords: migration; suburbanisation; city